Quantification of the forearm muscles mechanical properties using myotonometer: Intra- and inter-examiner reliability and its relation with hand grip strength - Tülay, C. S.; Ilke, K.; Seval Kutlurtürk, Y. (Journal of Electromyography and Kinesiology, 2022)
The primary objective of this study was to investigate the reliability of the myotonometer in the mechanical properties of the forearm muscles [m. extensor carpi radialis brevis (ECRB), and m. flexor carpi ulnaris (FCU)] in healthy individuals. The secondary objective was to investigate the relationship between the handgrip strength and mechanical properties of these forearm muscles. The mechanical properties (muscle tone, stiffness, and elasticity) of the ECRB and FCU were measured using the MyotonPRO device. Examiner 1 performed two sets of measurements with a time interval of 30 min to determine intra-examiner reliability. Examiner 2 performed measurements during the interval between the two sets of examiner 1. The intra- and inter-examiner reliabilities were excellent (ICC?0.82) for muscle tone, stiffness, and elasticity of the FCU. Both intra- and inter-examiner reliability in the evaluation of ECRB muscle tone, elasticity, and stiffness was moderate to excellent (ICCs = 0.56-0.98). The muscle tone and stiffness properties of the FCU were positively correlated with the handgrip strength (p <.05). The study findings indicate that the MyotonPRO device is a reliable tool to quantify ECRB, and FCU muscles mechanical properties in healthy individuals.